Regional Urban Systems in the Roman World, 150 BCE - 250 CE - Ligt, Luuk de (Mnemosyne, Supplements Ser, 2019)
Intro -- ‎Contents -- ‎Acknowledgements -- ‎Figures and Tables -- ‎Abbreviations -- ‎Notes on Contributors -- ‎Chapter 1. Introduction (de Ligt and Bintliff) -- ‎Chapter 2. A World of 200 Oppida: Pre-Roman Urbanism in Temperate Europe (Fernández-Götz) -- ‎Chapter 3. The Size Distribution of Self-governing Cities in the North-Western Provinces: Trends and Anomalies (Pellegrino) -- ‎Chapter 4. The Roman 'Small Towns' in the Massif Central (civitates of the Arverni, Vellavii, Gabali, Ruteni, Cadurci and Lemovices): Methodology and Main Results (Baret) -- ‎Chapter 5. Towns, Roads and Development Dynamics in the Territory of the Arverni in Roman Times (Auvergne, France) (Trément, Baret, Dacko, Trescarte, Calbris, Augustin and Massounie) -- ‎Chapter 6. Urbanisation of the Iberian Peninsula during the Roman Period: Choices, Impositions and 'Resignation' of the Newcomers (Rodríguez Gutiérrez) -- ‎Chapter 7. The Urban Landscape of Roman Central Adriatic Italy (Vermeulen) -- ‎Chapter 8. The Impact of Roman Rule on the Urban System of Sicily (de Ligt) -- ‎Chapter 9. Roman Towns and the Settlement Hierarchy of Ancient North Africa: A Bird's-Eye View (Hobson) -- ‎Chapter 10. A Diachronic and Regional Approach to North African Urbanism (Stone) -- ‎Chapter 11. Micro-regional Urbanism: An Ancient Urban Landscape in Roman North Africa (Scheding) -- ‎Chapter 12. Urbanisation and Population Density: The Case of the 'Small Municipia' in the Balkan and Danube Provinces (Donev) -- ‎Chapter 13. Between the River and the Fort: Applying Critical Regionalism to Roman Towns in the Pannonian Basin (Mladenović) -- ‎Chapter 14. Urban Networks in Early Roman Macedonia and Aegean Thrace (Karambinis) -- ‎Chapter 15. Regional Perspectives on Urbanism and Settlement Patterns in Roman Asia Minor (Willet).